GENERATOR PEMBANGKIT PLASMA DENGAN KONFIGURASI ELEKTRODA BATANG TIPIS DAN JARUM - Wardaya, Asep Yoyo; Nur, Muhammad (BERKALA FISIKA, 2015)
The application of plasma generator has been developed for everyday live because it can generate high electric field and induced current, even by only 12 volt of potential difference. The advantages of the plasma generator are mainly caused by configuration form of its electrodes which is usually very sharp and asymmetric form. In this paper, plasma generator has been discussed using electrodes configuration of the thin rod and needle in two dimensional planes. The result shows that the plasma generator can produce various high electric fields, which highest field at the tip of needle electrode. In case of configuration of needle electrode, it will be produced saturated current due to their asymmetric electrodes, while in case of thin rod electrode; it will be no saturated current due to symmetric electrode. Keywords: plasma generator, thin rod and needle configuration electrodes, electric field, saturated current.